Defensive and attacking performance indicators In Rugby Sevens - Ross, A.; Gill, N.; Cronin, J.; Malcata, R. (International Journal of Performance Analysis in Sport, 2016)
Rugby Sevens is a high intensity, intermittent team sport set to debut at the 2016 Olympic games. The purpose of this study was to determine the relationship between individual and team match actions and points scored and conceded. Individual and team match actions were analysed from 16 teams from 37 matches during an International Rugby Board Sevens World Series tournament as well as 50 matches from a single team across a season. Attacking and defensive performance indicators were modelled for their relationship with points scored and conceded, respectively, through general linear mixed-effects models. All attacking and defensive indicators had clear within and between-team effects on points scored and conceded. Line breaks had the strongest relationship with points scored with a two between-team standard deviation increase resulting in 12.2 (90% confidence limits ± 1.2) points scored while a two-between team standard deviation increase in tackle score resulted in 12.3 (90% confidence limits ± 1.8) fewer points conceded. Rugby sevens teams should seek to increase the number of line breaks per match while also increasing dominance in the tackles affected .